Comparison of Topical and Intravenous Tranexamic Acid for Total Knee Replacement: A Randomized Double-Blinded Controlled Study of Effects on Tranexamic Acid Levels and Thrombogenic and Inflammatory Marker Levels. (4th December 2019) - Jules-Elysee, Kethy M.; Tseng, Audrey; Sculco, Thomas P.; Baaklini, Lila R.; McLawhorn, Alexander S.; Pickard, Amanda J.; Qin, WeiGe; Cross, Justin R.; Su, Edwin P.; Fields, Kara G.; Mayman, David J.
Abstract : Background: Tranexamic acid (TXA) is an antifibrinolytic drug. Topical administration of TXA during total knee arthroplasty (TKA) is favored for certain patients because of concerns about thrombotic complications, despite a lack of supporting literature. We compared local and systemic levels of thrombogenic markers, interleukin (IL)-6, and TXA between patients who received intravenous (IV) TXA and those who received topical TXA. Methods: Seventy-six patients scheduled for TKA were enrolled in this randomized double-blinded study. The IV group received 1.0 g of IV TXA before tourniquet inflation and again 3 hours later; a topical placebo was administered 5 minutes before final tourniquet release. The topical group received an IV placebo before tourniquet inflation and again 3 hours later; 3.0 g of TXA was administered topically 5 minutes before final tourniquet release. Peripheral and wound blood samples were collected to measure levels of plasmin-anti-plasmin (PAP, a measure of fibrinolysis), prothrombin fragment 1.2 (PF1.2, a marker of thrombin generation), IL-6, and TXA. Results: At 1 hour after tourniquet release, systemic PAP levels were comparable between the IV group (after a single dose of IV TXA) and the topical group. At 4 hours after tourniquet release, the IV group had lower systemic PAP levels than the topical group (mean and standard deviation, 1, 117.8 ± 478.9 µg/L versus 1, 280.7 ± 646.5 µg/L; p = 0.049), indicative of higher antifibrinolytic activity after the second dose. There was no difference in PF1.2 levels between groups, indicating that there was no increase in thrombin generation. The IV group had higher TXA levels at all time points (p < 0.001). Four hours after tourniquet release, wound blood IL-6 and TXA levels were higher than systemic levels in both groups (p < 0.001). Therapeutic systemic TXA levels (mean, 7.2 ± 7.4 mg/L) were noted in the topical group. Calculated blood loss and the length of the hospital stay were lower in the IV group (p = 0.026 and p = 0.025). Conclusions: Given that therapeutic levels were reached with topical TXA and the lack of a major difference in the mechanism of action, coagulation, and fibrinolytic profile between topical TXA and a single dose of IV TXA, it may be a simpler protocol for institutions to adopt the use of a single dose of IV TXA when safety is a concern. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.